2018
DOI: 10.1177/0890334418776654
|View full text |Cite
|
Sign up to set email alerts
|

Do Breast Implants Influence Breastfeeding? A Meta-Analysis of Comparative Studies

Abstract: Participants with breast implants are less likely to establish breastfeeding, especially exclusive breastfeeding. Periareolar incision does not appear to reduce the exclusive breastfeeding rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
1
9
0
2
Order By: Relevance
“…These procedures often sever milk ducts, thus disrupting milk removal and, over time, potentially isolating glandular tissue, causing milk stasis and ultimately apoptosis and regression of the tissue. Alternatively, in some instances breast implants may have been inserted into breasts that were already hypoplastic [73][74][75][76].…”
Section: Breast Anatomy and Milk Productionmentioning
confidence: 99%
“…These procedures often sever milk ducts, thus disrupting milk removal and, over time, potentially isolating glandular tissue, causing milk stasis and ultimately apoptosis and regression of the tissue. Alternatively, in some instances breast implants may have been inserted into breasts that were already hypoplastic [73][74][75][76].…”
Section: Breast Anatomy and Milk Productionmentioning
confidence: 99%
“…For persons with breast implant surgery, Cheng and colleagues showed a somewhat higher incidence of impaired lactation in their meta‐analysis of 5 studies 55 . The studies included 1165 women with implants and more than 40,000 women without implants who served as control subjects in the studies.…”
Section: Glandular Causes Of Insufficient Lactationmentioning
confidence: 99%
“…The summary results were dominated by the hospital discharge study by Roberts et al, which included 378,389 persons 56 . Those with implants had a 39% decreased risk of exclusive breastfeeding (relative risk [RR], 0.63; 95% CI, 0.46‐0.86) and a 22% decrease in any breastfeeding (RR, 0.88; 95% CI, 0.81‐0.95) 55 . Jewell et al followed 4600 people who gave birth after a breast implant and found that 79% breastfed and 20% identified they had insufficient milk supply 57 .…”
Section: Glandular Causes Of Insufficient Lactationmentioning
confidence: 99%
“…But most studies focused on the impact of breast implant on breastfeeding. [2,57] The association between breast implant in mother and adverse outcomes in offspring was rarely studied at early stage until some hospitalized cases of children probably induced by breastfeeding by mother with breast implant were reported. [8–11] Fortunately, several studies of which the data were from the Nordic European countries present the impact of breast implant on the rate of morbidity in offspring.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Although the evidence on this association remained inconclusive due to small number of studies, limited statistical power and without quantitative meta-analysis, systematic review and meta-analyses have suggested that the women with breast implant are less likely to have exclusive breastfeeding. [6,7] It is plausible that breast implant may influence offspring's health by less breastfeeding in long term, because breastfeeding has been suggested as an independent protective factor on development and health of babies and psychological health of mothers. [15–18] Thus, it is necessary to conduct a comprehensive systematic review and meta-analysis to confirm whether breast implant in mother can increase the risk of long-term adverse health outcomes in offspring.…”
Section: Introductionmentioning
confidence: 99%